Ionosphere Sounding for Pre-seismic Anomalies Identification (INSPIRE): Results of the Project and Perspectives for the Short-Term Earthquake Forecast - Pulinets, Sergey; Krankowski, Andrzej; Hernandez-Pajares, Manuel; Marra, Sergio; Cherniak, Iurii; Zakharenkova, Irina; Rothkaehl, Hanna; Kotulak, Kacper; Davidenko, Dmitry; Blaszkiewicz, Leszek; Fron, Adam; Flisek, Pawel; et al. (Frontiers in Earth Science, 2021)
The INSPIRE project was dedicated to the study of physical processes and their effects in ionosphere which could be determined as earthquake precursors. It was initiated by ESA and carried out by an international consortium. The set of the ionospheric plasma key parameters was selected based on the retrospective analysis of the ground-based and satellite measurements of pre-seismic anomalies. Using this classification the multi-instrumental database of worldwide ionospheric measurements (Ionosonde and GNSS networks, LEO-satellites with in situ probes including DEMETER and FORMOSAT/COSMIC ROC missions) was developed for selected test cases. Statistical processing shows, main ionospheric precursors appear approximately 5 days before the earthquake. Physical mechanisms of the ionospheric pre-seismic anomalies generation from ground to the ionosphere altitudes were formulated within framework of the Lithosphere-Atmosphere-Ionosphere Coupling (LAIC) model. The precursor’s development was analyzed from crustal movements, radon emission, air ionization, thermal and atmospheric anomalies, electric field and electromagnetic emissions generation to variations of ionospheric plasma parameters. Assessment of the LAIC model performance with definition of performance criteria for earthquake forecasting probability has been done in statistical and numerical simulation domains of the Global Electric Circuit. Simulations of the earthquake preparation process confirms that the ionospheric precursors are one of the latest in the sequence of precursors. The work presents the general algorithm for the ionospheric precursors identification, including possible factors generating false alarms, emphasizing the importance of the special stable pattern called the “precursor mask” as well as the role of expert decision in pre-seismic anomalies interpretation for the seismic warning. Performance of the LAIC seismo-ionospheric effect detection module has been demonstrated using the case study of L’Aquila 2009 earthquake. Results of INSPIRE project demonstrated that the ionospheric anomalies registered before the strong earthquakes could be used as reliable precursors. The detailed classification of the pre-seismic anomalies was presented in different regions of the ionosphere and signatures of the pre-seismic anomalies were described into a clear methodology of the precursor’s identification from ionospheric multi-instrumental measurements. Configuration for the dedicated multi-observation experiment and satellite payload was proposed for the future implementation of the INSPIRE project results, including space equipment and ground-based support.